Mean Platelet Volume and Platelet Distribution Width Are Associated with Gallbladder Cancer - Zhang, Xin (Asian Pac J Cancer Prev, 2018)
Gallbladder cancer (GBC) represents the most common biliary tract malignancy. Activated platelets play an essential role in cancer development and progression. Mean platelet volume (MPV) and platelet distribution width (PDW) are commonly used indexes of activated platelets in clinical practice. The aim of the current study was to investigate the association of MPV and PDW with GBC. 104 GBC patients and 109 normal control subjects were entered in this study between January 2015 and December 2015. We collected all participants’ clinical and laboratory characteristics at initial diagnosis. The odds ratios (ORs) for GBC were calculated using multivariate logistic regression analysis after adjusting for confounding variables across MPV and PDW quartiles. MPV levels were markedly lower and PDW levels were remarkably higher in GBC patients than control subjects. A significant correlation between PDW and lymph node metastasis was detected. In addition, after adjusting for other risk factors, the ORs (95% CIs) for GBC in each MPV quartile were 5.117 (1.939-13.506), 2.444 (0.917-6.516), 3.718 (1.381-10.007), and 1.000, respectively. The ORs (95% CIs) for GBC in each PDW quartile were 1.000, 2.063 (0.825-5.162), 3.070 (1.108-8.507), and 12.108 (4.243-34.553), respectively. In conclusion, decreased MPV and elevated PDW were independently associated with GBC. Our findings suggest that MPV and PDW are available parameters for early detection of GBC.